III Research Evaluation Seminar in SSD ICAR/17-Disegno. Disciplinary Strategies and Policies (diségno, 2022)
On 12 May in the Aula Magna of the Faculty of Architecture in Valle Giulia, the III Research Evaluation Seminar in SSD ICAR/17-Disegno. Disciplinary strategies and policies was held, organized by the Commission on Scientific Production and Evaluation jointly with the Innovation Commission of the UID. [read more]